Mapping the Intellectual Landscape of Prophetic Literature: A Comprehensive Bibliometric Analysis - Putra, Candra Rahma Wijaya; Sunaryo, Hari; Hiasa, Fina (Humanus, 2025)
Prophetic literature is literature with a pattern of transcendence. The history of literature in Indonesia has many prophetic literary works. Prophetic literature has the purpose of introducing prophetic values. The purpose of this research is to make a research mapping of prophetic literature globally. The goal is to map developments, trends, and research opportunities about prophetic literature. A bibliometric analysis was conducted to examine prophetic literature publications from the Scopus database. Using the search terms "prophetic literature" and "prophetic education," a search from 1939 to 2024 yielded 133 publications. The data source was then focused on 66 publications in the form of articles and conference papers. The results of this research analysis, first, the results of the performance analysis show that prophetic literature research has been carried out from 1939 to 2024. Based on the citation analysis, there are 3 articles that are often referenced. The three articles have a tendency to use prophetic literature as a medium for conveying values and propaganda narratives. Second, there are future research offerings, especially with an emphasis on interdisciplinary perspectives. This is related to prophetic literature that intersects with politics, theology, history, and literature.